Splenunculectomy in thrombocytopenic purpura. Issue 2 (February 1986) - Reid, M M; Saunders, P W; Fenwick, J D; Walker, W
Abstract : In six patients with thrombocytopenic purpura not cured by splenectomy platelets fell to less than 150 X 10(9)/l within six weeks of splenectomy. They 'failed to respond'. Two underwent splenunculectomy without improvement. Splenuculectomy offered little chance of improvement to published cases who failed to respond but may well be helpful after true relapse.